Business metadata with the STA data modelling technique - Mohamed, Ibrahim; Noordin, Mohamad Fauzan (2011)
Business process management are increasingly important and being used in business, and offers effective and efficient operations. Business process modelling is a way of representing an organisation to enable its analysis and improvement. Business metadata is very helpful for businessperson, and also can act as a communication tool between them and technical IT people. STA (Source- Transaction-Agent) data model is introduced as a modelling technique for business metadata. STA data model uses business metadata to assist businessperson to participate in business data modelling of a system development process. This paper shows the success of implementing the STA data model. A research is conducted via workshops on 175 participants (they were grouped into smaller groups for effective outcome). The results show that STA data model is an effective and efficient data modelling technique. The participants can participate in the process as terms used are familiar and business-friendly.